High energy density single-crystal NMC/Li6PS5Cl cathodes for all-solid-state lithium-metal batteries - Doerrer, C; Capone, I; Narayanan, S; Liu, J; Grovenor, CRM; Pasta, M; Grant, PS (American Chemical Society, 2021)
To match the high capacity of metallic anodes, all-solid-state batteries require high energy density, long-lasting composite cathodes such as Ni-Mn-Co (NMC)-based lithium oxides mixed with a solid-state electrolyte (SSE). However in practice, cathode capacity typically fades due to NMC cracking and increasing NMC/SSE interface debonding because of NMC pulverization, which is only partially mitigated by the application of a high cell pressure during cycling. Using smart processing protocols, we report a single-crystal particulate LiNi0.83Mn0.06Co0.11O2 and Li6PS5Cl SSE composite cathode with outstanding discharge capacity of 210 mA h g-1 at 30 °C. A first cycle coulombic efficiency of >85, and >99% thereafter, was achieved despite a 5.5% volume change during cycling. A near-practical discharge capacity at a high areal capacity of 8.7 mA h cm-2 was obtained using an asymmetric anode/cathode cycling pressure of only 2.5 MPa/0.2 MPa.